Phenotypic characterization of disease‐initiating stem cells in JAK2‐ or CALR‐mutated myeloproliferative neoplasms. Issue 5 (9th March 2023) - Ivanov, Daniel; Milosevic Feenstra, Jelena D.; Sadovnik, Irina; Herrmann, Harald; Peter, Barbara; Willmann, Michael; Greiner, Georg; Slavnitsch, Katharina; Hadzijusufovic, Emir; Rülicke, Thomas; Dahlhoff, Maik; Hoermann, Gregor; et al.
Abstract: Myeloproliferative neoplasms (MPN) are characterized by uncontrolled expansion of myeloid cells, disease‐related mutations in certain driver‐genes including JAK2, CALR, and MPL, and a substantial risk to progress to secondary acute myeloid leukemia (sAML). Although behaving as stem cell neoplasms, little is known about disease‐initiating stem cells in MPN. We established the phenotype of putative CD34 + /CD38 − stem cells and CD34 + /CD38 + progenitor cells in MPN. A total of 111 patients with MPN suffering from polycythemia vera, essential thrombocythemia, or primary myelofibrosis (PMF) were examined. In almost all patients tested, CD34 + /CD38 − stem cells expressed CD33, CD44, CD47, CD52, CD97, CD99, CD105, CD117, CD123, CD133, CD184, CD243, and CD274 (PD‐L1). In patients with PMF, MPN stem cells often expressed CD25 and sometimes also CD26 in an aberrant manner. MPN stem cells did not exhibit substantial amounts of CD90, CD273 (PD‐L2), CD279 (PD‐1), CD366 (TIM‐3), CD371 (CLL‐1), or IL‐1RAP. The phenotype of CD34 + /CD38 − stem cells did not change profoundly during progression to sAML. The disease‐initiating capacity of putative MPN stem cells was confirmed in NSGS mice. Whereas CD34 + /CD38 − MPN cells engrafted in NSGS mice, no substantial engraftment was produced by CD34 + /CD38 + or CD34 − cells. The JAK2‐targeting drug fedratinib and the BRD4 degrader dBET6 induced apoptosis and suppressed proliferation in MPN stem cells. Together, MPN stem cells display a unique phenotype, including cytokine receptors, immune checkpoint molecules, and other clinically relevant target antigens. Phenotypic characterization of neoplastic stem cells in MPN and sAML should facilitate their enrichment and the development of stem cell‐eradicating (curative) therapies.